The Effect of Product Variety on Inventory Turnover in Different Modes of Operation - Junaid Ali Khan; Shiming Deng; Muhammad Hammad A.K. Khan (European Scientific Journal, ESJ, 2017)
We study the effects of product variety on operational metrics - inventory turnover and on sales in different mode of operations. Research has shown that performance metrics can vary in different mode of operations. Using 41 months of data from a large retailer, we show that correlation of product variety with inventory turnover and sales is not always negative or positive as shown in previous studies. This correlation can vary depending upon the mode of operations and type of product. Our study highlights impact of increased product variety on inventory turnover and sales in different mode of operations that has previously been overlooked in studies of retail product variety and inventory management. It also quantifies the impact of product variety on inventory turnover and sales.